2016
DOI: 10.1179/1753555715y.0000000059
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and photocatalytic activity of MAO–TiO2films formed on titanium doped with cations

Abstract: The microarc oxidation (MAO) TiO 2 films were fabricated in phosphate based electrolyte under different voltages on titanium to study the optimum voltage for photocatalysis, and then the doping process was carried out under the optimum condition above. The surface morphology and composition of MAO films were examined by scanning electron microscopy and X-ray diffraction. The photocatalytic activities of MAO films with and without cation dopant were evaluated by photocatalytic decolourisation of methylene blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A similar phase transformation was observed in the PEO coatings obtained with the DC voltages in the range of 250–550 V in aqueous solution of sodium phosphate(V). It was also found that the use of additional stage of functionalization of the PEO coating through a 20-h exposure in baths containing selected cations of transitional metals (Ti 4+ , Cr 3+, Zn 2+ , Ni 2+ , Co 3+ , Fe 3+ and Cu 2+ ) or rare earth metals (Dy 3+ , Nd 3+ , La 3+ and Ce 4+ ), in each case, improved the photocatalytic properties of the PEO surfaces [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…A similar phase transformation was observed in the PEO coatings obtained with the DC voltages in the range of 250–550 V in aqueous solution of sodium phosphate(V). It was also found that the use of additional stage of functionalization of the PEO coating through a 20-h exposure in baths containing selected cations of transitional metals (Ti 4+ , Cr 3+, Zn 2+ , Ni 2+ , Co 3+ , Fe 3+ and Cu 2+ ) or rare earth metals (Dy 3+ , Nd 3+ , La 3+ and Ce 4+ ), in each case, improved the photocatalytic properties of the PEO surfaces [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) has been synthesised by different methods including sol-gel [11,12], hydrothermal process [13], physical/chemical vapour deposition [14][15][16] and annealing [17] and micro-arc oxidation (MAO) [18][19][20][21]. Among these methods, the most promising and environmentally friendly technology seems to be micro-arc oxidation (MAO), the process was characterised by spark micro-discharges which move rapidly on the vicinity of the anode surface [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Among them, plasma electrolytic oxidation (PEO) has been widely investigated in recent years as an environmentally friendly technology for preparing ceramic coatings on valve metals (such as Al, Mg and Ti) to restrict the directly contact with our environment. [11][12][13][14] The process of PEO is carried out at voltages higher than the breakdown voltage of the gas layer enshrouding the anode. Since the alloy substrate is connected to positive pole of the rectifier as anode, the gas layer consists of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…911 Among them, plasma electrolytic oxidation (PEO) has been widely investigated in recent years as an environmentally friendly technology for preparing ceramic coatings on valve metals (such as Al, Mg and Ti) to restrict the directly contact with our environment. 1114…”
Section: Introductionmentioning
confidence: 99%